2006
DOI: 10.1002/adma.200500181
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective Functionalization of Carbon Nanotubes

Abstract: Carbon nanotubes (CNTs) are attractive nanodevice components due to their unique electronic structure, molecular dimensions, and shape.[1] The remarkable structural integrity of CNTs [2] and progress in techniques to assemble them into mesoarchitectures [3] make them attractive templates to assemble other low-dimensional structures (e.g., nanoparticles, biomolecules) to create hybrid nano-and mesostructures, composites, [4] and devices. Hybrid structures allow access to new electronic, electrical, and magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…One of most widely used techniques for defect identification in covalently bonded carbon, 24,[27][28][29]150,151 BN, 152 or Si ͑Refs. 65, 153, and 154͒ nanostructures is Raman scattering.…”
Section: Experimental Techniques Used To Identify Defects In Nanmentioning
confidence: 99%
See 3 more Smart Citations
“…One of most widely used techniques for defect identification in covalently bonded carbon, 24,[27][28][29]150,151 BN, 152 or Si ͑Refs. 65, 153, and 154͒ nanostructures is Raman scattering.…”
Section: Experimental Techniques Used To Identify Defects In Nanmentioning
confidence: 99%
“…Experiments on electron 72 and ion 334 24. ͑Color online͒ Sequential TEM images of the interlayer defects which appear and disappear in DWNTs recorded at 573 K. In the ͓͑a͒-͑d͔͒ side wall, several bridges connecting two graphene layers frequently appear in dark contrast ͑marked by red arrows͒ and disappear just after the observation.…”
Section: Annealing Of Irradiation-induced Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14] Another important issue is the role of structural defects, which can act as active centers promoting the oxidation and/or favoring the formation of certain functional groups. In fact, even the highest quality CNTs contain various structural defects, [17] which can alter their electrical, [18] transport, [19] and chemical [20,21] properties. In a recent study, we showed that the C 1s core level spectrum is an excellent fingerprint for the structural quality of C-based materials.…”
mentioning
confidence: 99%